Current and future in FHR monitoring - Okai, Takashi (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3126/njog.v2i2.1465 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 86 - 88